2012
DOI: 10.1002/anie.201205097
|View full text |Cite
|
Sign up to set email alerts
|

Total Spontaneous Resolution by Deracemization of Isoindolinones

Abstract: Separated: 3-hydroxy-3-phenylisoindolin-1-ones have been resolved by dynamic preferential crystallization. The compounds were effectively racemized through ring-opening and ring-closing reactions via achiral intermediates under basic conditions. Crystallization from a toluene solution containing 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) with stirring and evaporation of the solvent gave optically active crystals quantitatively with high ee values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 39 publications
0
57
1
Order By: Relevance
“…11b). 41 Some of the present authors later reported that the isoindolinones can be deracemised completely through Viedma ripening provided that (1) there is sufficient attrition, (2) a suitable solvent is used in which the compounds have a high enough solubility and (3) that racemization is avoided during the ee analysis. Another class of compounds that can be obtained in enantioenriched form through total spontaneous resolution are isoindolinones (Fig.…”
Section: (4) Recent Examplesmentioning
confidence: 74%
“…11b). 41 Some of the present authors later reported that the isoindolinones can be deracemised completely through Viedma ripening provided that (1) there is sufficient attrition, (2) a suitable solvent is used in which the compounds have a high enough solubility and (3) that racemization is avoided during the ee analysis. Another class of compounds that can be obtained in enantioenriched form through total spontaneous resolution are isoindolinones (Fig.…”
Section: (4) Recent Examplesmentioning
confidence: 74%
“…Progression of the reaction leads to the supersaturation of 1 in the solution, which induces the spontaneous crystallization of 1. Since amino nitrile in solution phase is almost racemic, spontaneous resolution and deracemization 19 are included. S1, ESI †).…”
mentioning
confidence: 99%
“…Recently it was reported by Yagishita et al. that 3‐hydroxy‐3‐phenylisoindolin‐1‐ones 1 – 3 (Figure 2) crystallize as conglomerate crystals and can also rapidly racemize in solution using 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as a catalyst through an intramolecular equilibrium reaction via an achiral intermediate 9. This enabled access to all three isoindolinones in high yield and high enantiomeric excess ( ee ) through preferential crystallization from solution (i.e.…”
mentioning
confidence: 99%
“…This enabled access to all three isoindolinones in high yield and high enantiomeric excess ( ee ) through preferential crystallization from solution (i.e. total spontaneous resolution) 9. The conglomerate behavior of these compounds should also allow the deracemization of an initial racemic solid state through Viedma ripening (Figure 1), which is a fundamentally different approach to reach an enantiopure end state as compared to total spontaneous resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation